PENINGKATAN KOMPETENSI GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SMK NEGERI 3 TABANAN - Dewa Made Wardika Yusana (Widyadari, 2023)
The research conducted is a school action research (PTS) which raises questions about how teachers can use existing learning media in the learning process in the classroom with the intention of increasing the quality of learning conducted in class and the evaluation is carried out through supervising activities of the principal in class when learning. This school action research activity was carried out at Tabanan 3 Public Vocational School for 3 months, from March to May 2021 by going through cycle stages. The purpose of this school action research (PTS) is to find out to what extent the supervision carried out by the school principal followed by the provision of guidance/treatment of target teachers can increase the competence of these teachers in applying learning models in class. In school action research (PTS) this was carried out in 2 cycles, the results of the actions taken proved to be able to increase teacher competence by achieving ideal standards. In the first cycle, the increase in teacher competence after classroom supervision after coaching on the use of learning media only reached around 33.33% in cycle II, which could increase to 100%. The average score obtained after class supervision in cycle I was 63.30 and increased in cycle II to 83.33, meaning that there was an increase of 20.03 and the level of completeness as a group/classical in cycle I reached 33.33% and in cycle II increased to 100%. The results of this school action research show that school principal coaching can improve teacher competence in using instructional media in the learning process.